Post-Partum Intrauterine Contraceptive Device: Experience from Tertiary Care Hospital in Sindh Province Pakistan - Nisar, Nusrat; Dars, Saira; Awan, Shazia; Jokhio, Farhat (Journal of Liaquat University of Medical & Health Sciences, 2020)
Contraceptive Device (PPIUCD) in women at tertiary care hospital at Pakistan. Methodology: Retrospective review of records of 2012 women who received PPIUD at Department of Obstetrics and Gynecology at Liaquat University of Medical and Health Sciences Jamshoro from August 2014 to July 2016. Sample was selected using non probability convenient sampling technique and included all the women who were offered PPIUCD during the above given period. Demographic and reproductive information was recorded. Women’s satisfaction with PPIUCD and problems related to it were noted at 6 weeks follow up. Data was analyzed using SPSS v 16. Results: During given time 27,180 women were delivered and 8,003 women were counseled for PPIUCD out of which 2,012 patients agreed for PPIUCD. Acceptance rate for PPIUCD was 25.1%. The Mean age ± SD and mean parity ± SD 29.8 ± 3.68 years and 3.1±2.17 respectively. PPIUCD was placed during postplacental and postpartum period in 1271(63.1) and 268 (13.3%) women respectively. Out of 1311 who returned for follow up 1238(94.4%) were satisfied and 43(3.2%) requested for removal. Expulsion of PPIUCD was noted in only 83(6.3%) of woman. Conclusion: Women coming for health facility delivery were having high level of acceptance for PPIUCD. Majority of women were willing to continue it as a method of contraceptive due to fewer side effects and high level of satisfaction. Key Words: PPIUCD, Contraception, Postpartum FP.